Effects of equine chorionic gonadotropin dosage and its splitting in different days on reproductive performance of Nellore cows synchronized for timed-artificial insemination - Sales, A. F.F. [UNESP]; Cappellozza, B. I.; Vilela, E.; Claro Júnior, I.; Sá Filho, O. G.; Vasconcelos, J. L.M. [UNESP] (Elsevier, 2024)
This study evaluated the effects of dose of equine chorionic gonadotropin (eCG) and its splitting in different days of the synchronization protocol on reproductive performance of primiparous and multiparous Nellore cows. In the present study, 2,536 Nellore cows (1,634 primiparous and 902 multiparous) were assigned to receive in a 2 × 2 factorial design 1) an intravaginal progesterone (P4) device and 2.0 mg of estradiol benzoate (EB) on day −11, 12.5 mg (i.m.) of dinoprost tromethamine (PGF), 300 IU (i.m.) of eCG, 0.6 mg (i.m.) of estradiol cypionate (ECP), and P4 device withdrawal on day −2, followed by TAI on day 0 (n = 632 cows, being 409 primiparous and 223 multiparous; 300–2), 2) 300 IU (i.m) of eCG administered on days −4 and −2 (150 IU of eCG/day; n = 637 cows, being 412 primiparous and 225 multiparous; 300-4-2), 3) 400 IU (i.m.) of eCG administered on day −2 (n = 633 cows, being 406 primiparous and 227 multiparous; 400–2), and 4) 400 IU (i.m) of eCG administered on days −4 and −2 (200 IU of eCG/day; n = 634 cows, being 407 primiparous and 227 multiparous; 400-4-2). Individual cow BCS was assessed on days −11, 0 (timed-AI), and 31 of the study. Body condition score of the animals was classified into LOW or HIGH using the threshold of 2.75 (≤2.75 = LOW; >2.75 = HIGH). For primiparous cows, an eCG splitting effect was observed on follicle size, as cows receiving eCG on days −4 and −2 of the synchronization protocol had a larger follicle than cows administered eCG only on day −2. For day 31 P/AI, primiparous cows receiving 400-4-2, regardless of BCS, had a greater P/AI than cows from other treatments. Administering 400-4-2 to LOW BCS cows also resulted in greater P/AI than all other treatments assigned to LOW BCS cows. For multiparous cows, no treatment effect was observed for follicle size, estrus expression, and day 31 P/AI (P ≥ 0.21). In summary, increasing the dose and splitting the dose of eCG positively impacted the pregnancy rates of primiparous cows under a BCS ≤2.75, but no effects were detected on multiparous cows.
Keywords: Body condition score; Equine chorionic gonadotrophin; Pregnancy per AI; Primiparous